COMMUNICATIVE LANGUAGE TEACHING IN ENGLISH LANGUAGE TEACHING: THEORETICAL FOUNDATIONS, PRACTICAL APPLICATIONS, AND CONTEMPORARY PEDAGOGICAL PERSPECTIVES - Mahmudjonova Ezoza Zafar qizi, (TADQIQOTLAR, 2026)
Abstract: Communicative Language Teaching (CLT) has emerged as one of the most influential and widely adopted methodological paradigms in the field of English Language Teaching (ELT) over the past five decades. Rooted in sociolinguistic and functional theories of language, CLT prioritizes the development of communicative competence over mere grammatical accuracy, thereby fostering learners» ability to use language  meaningfully  in  real-life  contexts.  This  paper  provides  a  comprehensive examination of CLT»s theoretical underpinnings, tracing its origins from Chomsky»s distinction  between  linguistic  competence  and  performance  to  Hymes»s communicative competence framework and Halliday»s functional linguistics.